Atribusi Kegagalan Berprestasi Siswa SMP dan SMA - Mohamad Iksan (Jurnal Psikologi Tabularasa, 2015)
This study aims to explore the failure attribution of junior high and high school students. This research uses indigenous psychology approach with qualitative survey method. The data retrieval technique using open ended questionnaire. Total 725 respondents consist of 248 junior high students and 473 high school students. Data obtained shows that failing achievement attribution was influenced by internal and external attribution. The highest failure achievement attribution of 79 is the internal attribution on junior high students it characterized by low self-possessed social skill. On senior high it counts to 87,1% on internal attribution. The external factors tend to be marked by the lack of social support from family or friends and teachers and friends negative influence.